A Case of Pregnancy Complicated with ATIII Deficiency in a Patient Who Developed Severe Venous Thromboembolism in Her Fourth Pregnancy and Had a Favourable Outcome in Her Subsequent Pregnancy with Careful Management of Anticoagulation Therapy including Edoxaban - Mie Sakai; Jumpei Ogura; Koji Yamanoi; Takahiro Hirayama; Tsutomu Ohara; Haruka Suzuki; Yoshihide Inayama; Koji Yasumoto; Koh Suginami (Case Reports in Obstetrics and Gynecology)
Congenital ATIII deficiency is one of the congenital thrombophilia diseases that can cause severe venous thromboembolism (VTE) in pregnant patients. A 30-year-old female, 4 gravida and 2 para, came to the emergency department with a complaint of oedema and pain in the left lower leg at 11 weeks of gestation. An inferior vena cava thrombus and pulmonary embolism were found. Because VTE was very severe, artificial abortion was performed, and VTE disappeared rapidly. She maintained oral administration of edoxaban (NOAC) and got pregnant naturally fifty-five weeks later after the abortion. Anticoagulation therapy was changed from NOAC to ATIII formulation and unfractionated heparin at 5 weeks of gestation. The course of pregnancy was good, and a healthy female newborn of 2310 g was delivered vaginally at 37 weeks 6 days of gestation. In puerperium, anticoagulation therapy was changed to warfarin. Currently one and one-half years had passed after delivery and no major adverse events or thrombosis has occurred. This case indicates that severe VTE can develop even in multipara pregnancy and that those who take NOAC may be able to continue pregnancy when they get pregnant.